Organizational culture and workplace well-being in a higher education institute, Arequipa case (Peru) (Revista Innova Educación, 2024)
The variables of organizational culture and occupational well-being have gained greater relevance, which is why workers must be familiar with these concepts. In the analyzed higher education institute, it was observed that an environment conducive to the development of staff capabilities is not fostered, negatively impacting occupational well-being. This generates an unmotivating work climate, making it difficult to develop a sense of belonging to the organization. Therefore, the study aimed to determine the relationship between organizational culture and occupational well-being among teachers at a higher education institute in the city of Arequipa in 2025. This was a basic research study developed under a quantitative approach and a non-experimental design. The population consisted of 42 teachers from the institute, and a non-probabilistic convenience sampling method was used. A single structured questionnaire with 25 items was employed as the measurement instrument, assessing both study variables. The results showed that both variables are at a medium level. Some teachers do not perceive sufficient autonomy in their work, and deficiencies were found in factors such as the work climate and conflict tolerance, which should be addressed to build a better culture aligned with the institution's objectives and teachers' expectations. Finally, it was concluded that there is a positive and significant relationship between organizational culture and occupational well-being among teachers at the higher education institute in Arequipa.
Keywords: work environment; quality of work life; work culture; educational management; higher education